Correlations Between Different Angiogenic and Inflammatory Factors in Vitreous Fluid of Eyes With Proliferative Diabetic Retinopathy - Wu, Guanrong; Liu, Baoyi; Wu, Qiaowei; Tang, Changting; Du, Zijing; Fang, Ying; Hu, Yijun; Yu, Honghua (Frontiers in Medicine, 2021)
Purpose: To investigate the expression of various angiogenesis and inflammation mediators in the vitreous fluid of eyes with proliferative diabetic retinopathy (PDR). Methods: A total of 38 eyes with PDR and 37 control eyes were included. Vitreous fluid was collected during vitrectomy. Vitreous levels of interleukin-34 (IL-34), colony stimulating factor-1 receptor (CSF-1R), syndecan-1, placental growth factor (PIGF), and angiopoietin-like protein 4 (ANGPTL-4) were measured by Luminex assays. Vitreous levels of vascular endothelial growth factor (VEGF), interleukin-6 (IL-6), interleukin-8 (IL-8), monocyte chemotactic protein-1 (MCP-1), tumor necrosis factor-α (TNF-α) and intercellular adhesion molecule-1 (ICAM-1) were measured by ELISA. Levels of these mediators were compared between the PDR and control eyes. Correlations between levels of different mediators and between these mediators and kidney function metrics in the PDR group were also analyzed. Results: Vitreous levels of syndecan-1, PIGF, ANGPTL-4, VEGF, IL-8 and ICAM-1 were significantly higher in the PDR group compared to the control group (all p<0.05). Significant positive correlations were detected between levels of any two of the following mediators including syndecan-1, PIGF, ANGPTL-4, IL-8 and ICAM-1 (r=0.494 to 0.891, all p<0.05). Apart from VEGF, levels of these mediators were positively correlated with serum creatinine and blood urea nitrogen (r=0.425 to 0.834, all p<0.05), and negatively correlated with estimated glomerular filtration rate (r=-0.350 to -0.417, all p<0.05). Conclusions: Correlations between different angiogenesis and inflammation mediators were observed in eyes with PDR, suggesting cross-talks of different angiogenesis and inflammation pathways in the pathogenesis of PDR. The levels of angiogenesis and inflammation in PDR are correlated with kidney damage, indicating possible common pathways in diabetic retinopathy and nephropathy.